Implementing Reader-Response Theory: An Alternative Way of Teaching Literature Research Report on the Reading of Booker T Washington's Up from Slavery* - Trisnawati, Ririn Kurnia (English Education Department, Universitas Islam Indonesia, 2009)
Reader-response theory shifts the critical focus from a text to a reader. It diverts the emphasis away from the text as the sole determiner of meaning to the significance of the reader as an essential participant in the reading process and the creation of meaning. Thus, both explanations place a reader as an active participant along with the text in the production of interpretation of that literary work from the point of view of the reader-response theory.As a result, if teaching literature is to accommodate the students' role in making interpretation, it is supposed to place them as the active readers to interpret and shape the meaning of that particular literary works; it is not preaching or directing them into a specific meaning decided previously. Students as the active readers must be given opportunity and space to develop their opinion and argumentation to shape and define what a particular text means to them. Therefore, by understanding and applying reader-response theory in teaching and learning literature in the classroom, at the same time, teachers could have a different teaching and learning method e.g. learners-centered learning.This paper is going to depict how the understanding of a literary work's meaning and interpretation is composed by the readers—the students; how the students could function themselves as active readers who successfully manage to interpret the literary work based on their responses and how finally this particular group of readers could finally agree on the particular interpretation. Besides, it is to place students both as the readers and learners of a discussed literary work as the center of teaching and learning literature as they are the active agent to shape the literary work's meaning. By doing so, teachers are also the ones who encourage students to express their opinions, and eventually students' critical thinking could be embraced. Hence, teaching and learning literature could become an interactive and collaborative process.